Mindfulness-based retreat for mothers of paediatric heart transplant recipients: protocol for a pilot intervention study - Sara Ahola Kohut; Joanna Mitchell; Samantha J Anthony; Taylor Robertson; Heather Telfer; Mirna Seifert-Hansen (BMJ Open)
Introduction Mothers are often the primary caregivers for children requiring heart transplantation. Given that a mother’s ability to successfully cope with the demands of her caregiving role may be predictive of positive familial psychosocial outcomes, it is critical that maternal coping is assessed and supported in paediatric healthcare. Mindfulness-based programmes are proposed as one intervention that may enhance quality of life, improve distress tolerance and coping and reduce social isolation in caregiving populations. This pilot study aims to investigate: (1) the implementation success of a mindfulness-based retreat (MBR), and (2) the effectiveness of a MBR at improving quality of life, distress tolerance, coping and perceived social support for mothers of paediatric heart transplant recipients.Methods and analysis A convergent parallel, mixed-method design is proposed for this pilot, exploratory study. Twenty mothers will participate in this pilot MBR held at a resort in Ontario, Canada. Quantitative data will be obtained using five standardised instruments completed at three time points: (T1) 24-hours prior to the intervention, (T2) immediately on completion of the intervention, and (T3) three months post-intervention. Qualitative data will be collected from all participants both through semi-structured focus groups at T2 and individual telephone interviews at T3. Focus groups and individual interviews will be transcribed verbatim for thematic analysis. Quantitative and qualitative data will be merged and compared during interpretation to ensure that the intervention implementation and effectiveness of the MBR retreat are described with comprehensive accuracy. The primary outcomes will be feasibility in relation to implementation effectiveness and participants’ perception of social support for efficacy of the MBR intervention.Ethics and dissemination This study received Institutional Research Ethics Board approval from The Hospital for Sick Children (Number: 1000064719). Informed consent will be obtained prior to participant enrolment. Findings will be disseminated via conference presentations and submitted for publication in a peer-reviewed journal.